LINEAL: an electronic encyclopedia in linear algebra - Voevodin, V.V.; Voevodin, Vl.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2003)
This paper is devoted to an information system designed for the usage in Internet and for the operation with problem-oriented databases in those branches of science where the cause-and-effect relations are of prime importance. Linear algebra is taken as an example for presentation of the system. This approach can be applied to any other natural science.